Electroacupuncture Alleviates Mechanical Allodynia of a Rat Model of CRPS-I and Modulates Gene Expression Profiles in Dorsal Root Ganglia - Wang, Jie; Zheng, Xiaoli; Liu, Boyu; Yin, Chengyu; Chen, Ruixiang; Li, Xiaojie; Li, Yuanyuan; Nie, Huimin; Zeng, Danyi; He, Xiaofen; Jiang, Yongliang; Fang, Jianqiao; et al. (Frontiers in Neurology, 2020)
Complex regional pain syndrome type-I (CRPS-I) is chronic neurological disorder accompanied with devastating pain. Most conventional medical treatments lack effectiveness, making CRPS-I a challenging clinical condition. Electroacupuncture (EA) showed effectiveness in alleviating the pain symptoms of CRPS-I patients. However, the molecular mechanisms underlying EA’s therapeutic effect are still not well understood. Here, we established the rat chronic post-ischemic pain (CPIP) model to mimic CRPS-I and performed repetitive EA on bilateral hind limbs of the CPIP model rats. We then performed RNA-sequencing (RNA-Seq) to study the differences in gene expression, gene networks and molecular pathways in ipsilateral DRGs innervating the hind limb of the CPIP model rats with and without repetitive EA treatment. Our results found that repetitive EA treatment significantly alleviated mechanical allodynia in bilateral hind limbs of CPIP model rats. RNA-Seq analysis indicated that EA modulated the expression of multiple genes and gene networks in the DRGs of CPIP model rats. Further bioinformatics analysis identified the up-regulation of an array of genes involved in biological process such as neutrophil chemotaxis and immune response in the DRGs of CPIP model rats after EA treatment. Thus, these results suggest that EA may alleviate pain response in CPIP model rats via regulating multiple genes. Our work may help to further advance the understandings of the molecular mechanisms underlying EA’s therapeutic effects on CRPS-I and help to identify novel targets for CRPS-I treatment.